2001
DOI: 10.3201/eid0704.010412
|View full text |Cite
|
Sign up to set email alerts
|

Equine West Nile Encephalitis, United States

Abstract: After the 1999 outbreak of West Nile (WN) encephalitis in New York horses, a case definition was developed that specified the clinical signs, coupled with laboratory test results, required to classify cases of WN encephalitis in equines as either probable or confirmed. In 2000, 60 horses from seven states met the criteria for a confirmed case. The cumulative experience from clinical observations and diagnostic testing during the 1999 and 2000 outbreaks of WN encephalitis in horses will contribute to further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 10 publications
8
46
0
Order By: Relevance
“…Amongst fever, also depression, anorexia, colic or lameness can be one of the first recognized signs in diseased animals (Long, 2006). Hyperesthesia, teeth grinding, muscular tremor, photophobia and blindness have been observed in a small proportion of clinical cases (Murgue et al, 2001b; Ostlund et al, 2001; Abutarbush et al, 2004; Garcia-Bocanegra et al, 2011). Abnormal behavior such as depression, somnolence, disorientation, hyperexcitability and aggressive behavior as well as changes in personality have also been associated with WN infection in equids (Ostlund et al, 2001; Porter et al, 2003; Abutarbush et al, 2004; Long, 2006; Garcia-Bocanegra et al, 2011).…”
Section: Clinical Symptoms In Horsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst fever, also depression, anorexia, colic or lameness can be one of the first recognized signs in diseased animals (Long, 2006). Hyperesthesia, teeth grinding, muscular tremor, photophobia and blindness have been observed in a small proportion of clinical cases (Murgue et al, 2001b; Ostlund et al, 2001; Abutarbush et al, 2004; Garcia-Bocanegra et al, 2011). Abnormal behavior such as depression, somnolence, disorientation, hyperexcitability and aggressive behavior as well as changes in personality have also been associated with WN infection in equids (Ostlund et al, 2001; Porter et al, 2003; Abutarbush et al, 2004; Long, 2006; Garcia-Bocanegra et al, 2011).…”
Section: Clinical Symptoms In Horsesmentioning
confidence: 99%
“…Excellent illustrations of the clinical signs of WN disease in horses are given by the following video: http://www.youtube.com/watch?v=BJtVP5Bd5bs. The fatality rate in diseased animals is high in horses and ranges from 22% to 44% (Murgue et al, 2001a; Ostlund et al, 2001; Schuler et al, 2004; Garcia-Bocanegra et al, 2011). In the 2000 French equine epizootic, fever as well as paresis and paralysis in addition to ataxia were frequent clinical signs (Murgue et al, 2001b).…”
Section: Clinical Symptoms In Horsesmentioning
confidence: 99%
See 1 more Smart Citation
“…They become viremic but the viremia is not high enough for horses to serve as an amplifying host [71]. In the 1999 outbreak, 36% of the infected horses either died of WN or were euthanized [72]. Other studies reported a 22–28% mortality rate in horses [73,74].…”
Section: Wnv In Mosquitoes Birds and Horsesmentioning
confidence: 99%
“…In addition, together with an automated RNA extraction, real-time RT-PCR can be used in large-scale surveillance, and allows quantitative measurement of viral nucleic acids [42]. In several studies, molecular detection assays based on broadly reactive (degenerate) primers may be used for the simultaneous detection and quantification of distinct flaviviruses using species-specific and group-specific primers in a single reaction [40] or targeting the flavivirus consensus amplimers located at the RNA-dependent RNA polymerase domain of the NS5 protein [43].…”
Section: Wnv Detectionmentioning
confidence: 99%